Kingdom of Fantasy : The Keepers of the Empire - Book 14 - Stilton, Geronimo; Barozzi, Danilo; Clement, Emily (Translator) (New York, NY : Scholastic, Inc., 2021)
Drawn once again into the Kingdom of Fantasy, Geronimo discovers that the Land of Books is being threatened by a wave of grayness spreading from the Kingdom of Swamp Valley rotting books and turning all the characters gray, sad and worried--and it will be up to Geronimo, Winglet (daughter of Blossom and newly crowned empress), and the intrepid characters from fiction who join them along the way, to locate the source of this new evil and put a stop to it.
Keywords: Stilton, Geronimo -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Juvenile fiction; Magic -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Imaginary places -- Juvenile fiction; Adventure stories; Fantasy -- Juvenile fiction; Humorous Stories; Mice -- Fiction; Magic -- Fiction; Characters in literature -- Fiction; Quests (Expeditions) -- Fiction; Imaginary places -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Humorous Stories; Junior fiction